Multispiral Computed Tomography Comparative Analysis and Justification of Chronic Lung Disease Complications in Patients with Covid-19 Pneumonia - Borotov F.M; Rakhmonova G. E. (Scholars Digest Publishing, 2023)
The article presents the results of computed tomography, magnetic resonance imaging, ultrasound, chest x-ray in patients with COVID-19 pneumonia. A comparative analysis of the diagnostic information content of each of the methods of radiological examination was carried out. It has been determined that magnetic resonance imaging and ultrasound can be used as an alternative to computed tomography.
Keywords: X-ray diagnostics, computed tomography, magnetic resonance imaging, radiography, ultrasound, COVID-19 pneumonia.